Analisis Perbandingan Abnormal Return Dan Likuiditas Saham Sebelum Dan Sesudah Stock Split Pada Perusahaan Yang Terdaftar Di Bursa Efek Indonesia Periode 2010-2015 - Cindy Hadiwijaya dan Indra Widjaja (Universitas Tarumanagara, 2019)
This research aims to find out whether there is a significant difference in abnormal return and liquidity of shares before and after stock split for companies listed in Indonesian Stock Exchange during 2010-2015. 46 samples were obtained using purposive sampling method. The observation period is 10 days before and after stock split announcement. Hypothesis was tested by using Wilcoxon Signed Rank Test with significant level of 0.05. The result of this research shows that there is a significant difference in abnormal return before and after stock split, while there is no significant difference of share’s liquidity before and after stock split.